Western Arabo-Islamophobia: where and when will it end? - Hamad, Abdulsalam Ali (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Islam has been under intensive ongoing crusade for centuries. It has been made into what might be called the cause of all the problems and ills that afflict the world. Every Westerner with a political axe to grind is being given centre stage to pontificate on Islam. Western political leaders have also adopted an apocalyptic discourse to ratchet up their rhetoric so as to talk in God’s name of the holy struggle against evil: Islam. Attacks have, therefore, been carried out against Arabs and Muslims in the West for the one and only simple fact that they are Arabs and Muslims. Islam, in Western eyes, is thus an invalid religion that must be rooted out from the soul of the world. This paper will be seeking to rebut these allegations and claims, prove that the West’s blindness to the truth has led it to perceive Islam as incompatible with the principles, prerequisites, and civil ethics of the Western world, and with the world at large. and provide evidence that it was under the sky of Islam that the human mind had most fully flourished and developed some of its choicest gifts, had most deeply pondered on the greatest problems of life, and had found solutions for some of them which deserved the attention even of those who studied Plato and Kant. Ultimately, it will be illustrating that it is time to come out of the narrow shell of misrepresentation, hostile and oriental stereotype, parochialism and communalism, religious rancour, and politics, and illuminate the track of humanity by holding high the lamp of wisdom, by giving form and shape to the great and noble dreams that were cherished by the immortal prophets and philosophers of the past so that the whole world might declare that the light has come from the East and saved the West from doom and destruction.